Elevated ZNF704 expression is associated with poor prognosis of uveal melanoma and promotes cancer cell growth by regulating AKT/mTOR signaling - Jingting Luo; Haowen Li; Jingying Xiu; Jingyao Zeng; Zhaoxun Feng; Hanqing Zhao; Yang Li; Wenbin Wei (BMC, 2023)
Abstract Background Uveal melanoma (UM) is the most common intraocular malignancy in adults, with a poor survival prognosis. To date, limited understanding of UM's molecular mechanisms constitutes an obstacle to developing effective therapy. In this study, we examined key regulators mediating UM progression and their clinical relevance. Methods Transcriptomics of UM patients and cells were analyzed via RNA sequencing and bioinformatic analysis. Zinc finger protein 704 (ZNF704) was identified as prognosis-related biomarker for UM based on clinical characteristics and RNA-seq data from The Cancer Genome Atlas (TCGA). Gene expression was knocked down by specific shRNAs/siRNAs and overexpressed by transfection with plasmids inserted with investigated gene cDNA. Cell proliferation, viability and invasion abilities were determined by CCK8, colony formation and transwell assays, respectively. For cell cycle and apoptosis, cells were PI or PI/Annexin V-APC stained and analyzed by flow cytometry. Standard immunoblotting and quantitative RT-PCR were employed to assess the mRNA and protein abundance. To determine tumor growth in vivo, 4-week-old BALB/c-nu immune-deficient nude mice were inoculated with tumor cells. Results Analysis of differential expressed genes (DEGs) and survival analysis identified ZNF704 as a novel biomarker of UM. Prognostic analysis indicated ZNF704 as an independent predictor of UM overall survival. Expression of ZNF704 is elevated in UM tissues relative to adjacent normal choroid tissues. Knockdown of ZNF704 suppressed the growth and migration of UM cells and vice versa. In addition, expression of ZNF704 arrest UM cells at G0/G1 phase and inhibit cell apoptosis. RNA sequencing analysis indicated that SORBS3 were dysregulated after ZNF704 downregulation. Gene Set Enrichment Analysis (GSEA) revealed that upon ZNF704 knowndown, genes related with PI3K/AKT/mTOR, EMT and metastasis are enriched. Mechanistically, ZNF704 activates AKT/mTOR/glycolysis signaling pathway in UM cells. Moreover, expression of SORBS3 is downregulated by ZNF704 and knockdown of SORBS3 restored tumor cell viability in ZNF704 silenced cells. Conclusions ZNF704 predicts poor prognosis of UM and exhibit pro-oncogenic effect in UM progression in vivo and in vitro, mediated through AKT/mTOR signaling pathway and suppression of SORBS3 expression.